Management model by processes for science parks - Ana Maria Magalh\~aes Correia; Claudimar Pereira da Veiga (Cogent Business & Management, 2019)
Design Science Research (DSR) purports to be a guide for research oriented to finding solutions to problems and designing artifacts. The aim of this study is to propose its use in the proposition of a management model by processes intended for science parks. Four science parks located in Paraná State, Brazil, were analyzed by conducting a comparative case study. Semi-structured interviews were held with the managers of the parks and non-participant observation was used to become more familiar with the environment to be studied. The results suggest that in order to define a management model by processes for science parks, the use of DSR is feasible. It is also important to follow its stages of construction, identifying the parks' management activities, identifying and mapping business processes and the information systems that support them and proposing this integration in the organizational logic of Enterprise Architecture. This study contributes to the field by using DSR to define a management model by processes that expresses the relationships between business processes and information systems and how these should be articulated in the development of activities in the environments under study.
Keywords: 650; science parks; enterprise architecture; artifacts; management model